The denationalisation of healthcare: How to replace the NHS with a social health insurance model - Kristian Niemietz (Institute of Economic Affairs (IEA), 2024)
Until very recently, Britain's National Health Service used to be beyond argument. The reverence for the health service often precluded anything resembling a rational discussion around it: the social taboos were simply too strong. Yet over the past two years or so, this has begun to change. We can now quite regularly find articles in the mainstream media which openly criticise the NHS, and point to better alternatives. In particular, advocacy of Social Health Insurance (SHI) systems has become part of the mainstream debate. SHI systems are market-based, competitive and largely non-state systems, in which the role of the state is not to run healthcare facilities, but to insure universal access. In terms of clinical outcomes, these systems tend to outperform the NHS, and they have done so for as long as we have data. This is not simply the result of better funding. While examples of a wholesale switch from an NHS-type system to an SHI-type system are rare, they do exist. The Czech Republic and Slovakia did precisely that over the course of the 1990s, and eastern Germany did so in the early 1990s as part of the Reunification process. The example of the Netherlands is also instructive. They never had a national health service, but until the mid-2000s, they had a system which, while notionally private, was very NHS-like in practice. Since then, they have replaced that system with a competitive, market-based, private SHI system. None of these examples are easily transferable to the UK, but what they do show is that a transition from one healthcare system to another need not be especially disruptive. It can be done in an orderly fashion, and it has been successfully done.
Keywords: 330; Statutory health insurance; health care; health financing; Great Britain; Gesetzliche Krankenversicherung; Gesundheitswesen; Gesundheitsfinanzierung; Großbritannien